The Impact of Institutional Reforms in Water Management on the Poor in Pakistan (Water Nepal, 2003)
Institutional reforms in water management in the form of phased programmes in pilot areas are underway in Pakistan. The reform process was initiated in Bahawalnagar District in Punjab in 1994 and has since spread elsewhere. The reforms will have a far reaching impact on the agrarian socio-economic structure of Pakistan. ActionAid-Pakistan is analysing the likely effects of the reforms on the poor and marginalised segments of the rural population, especially in terms of their empowerment, participation in grassroot level development activities, food rights, security and the degree to which their livelihoods are sustainable.Water Nepal Vol.9-10, No.1-2, 2003, pp.361-367